Executive Functions in Parkinson’s Disease - Rossi,Tainá (2021)
Abstract The objective of this study was to investigate executive functions (EFs) in older adults with Parkinson’s disease (PD). It was a cross-sectional and comparative study, composed of 62 participants divided into PD group (n = 31; M age = 75.26; SD age = 7.26) and control group (n = 31; M age = 74.03; SD age = 6.95), aged 61 to 93 years, recruited for convenience in 5 cities in the state of Rio Grande do Sul. The instruments used were a sociodemographic data questionnaire; MMSE; GDS-15; BIS-11; verbal fluency tasks (FAS and animals), DEX; WCST-64 and FDT. Descriptive analyzes and Student’s t and Chi-square tests were used. The PD group had a lower performance in the WCST-64 and FDT tests compared to controls, indicating worse performance in tasks that required reasoning, cognitive flexibility and processing speed, in addition, showed difficulties in performing tasks that require EF (DEX).